Mindfulness untuk Mengatasi Kecemasan Ibu-ibu Penyintas Bencana Gempa Cianjur - Sri Mulyani Nasution; Astri Dwi Andriani; Erry Indriani; Esiyannera; Mukti Utama; Rizky Purnomo Adji Churnawan (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2024)
The earthquake disaster that devastated Cianjur on November 21, 2022, has left various problems for the people affected by the earthquake. Not only material losses, but psychological problems also arise and are felt by survivors who face difficult situations as a result of the disaster. As a form of community service, the Faculty of Psychology at Jayabaya University Jakarta in collaboration with Putra Indonesia Cianjur University (UNPI) participates in providing psychosocial assistance for disaster survivors. Through field observations which were followed up by measuring stress levels, the results showed that it was necessary to provide training to the community with a community approach in the form of Mindfulness training. The training has been given in 8 locations with different participants from 21 December 2022 to 4 January 2023.